2022
DOI: 10.1111/desc.13276
|View full text |Cite
|
Sign up to set email alerts
|

Age‐differences in network models of self‐regulation and executive control functions

Abstract: Self‐regulation (SR) and executive control functions (EF) are broad theoretical concepts that subsume various cognitive abilities supporting the regulation of behavior, thoughts, and emotions. However, many of these concepts stem from different psychological disciplines relying on distinct methodologies, such as self‐reports (common in SR research) and performance‐based tasks (common in EF research). Despite the striking overlap between SR and EF on the theoretical level, recent evidence suggests that correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 106 publications
6
7
0
1
Order By: Relevance
“…However, we not only specify the interrelationships cross-sectionally at the between-person level but also extend it to the temporal dynamics at the within-person level. Consistent with our results, Neubeck et al (2022) reported more relationships between self-control and emotion regulation compared to the associations with executive function (including response inhibition). This study had, however, been conducted on cross-sectional data at the between-person level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we not only specify the interrelationships cross-sectionally at the between-person level but also extend it to the temporal dynamics at the within-person level. Consistent with our results, Neubeck et al (2022) reported more relationships between self-control and emotion regulation compared to the associations with executive function (including response inhibition). This study had, however, been conducted on cross-sectional data at the between-person level.…”
Section: Discussionsupporting
confidence: 91%
“…Along these lines, Neubeck et al. ( 2022 ) examined the structure of cross‐sectional networks covering 12 self‐reported facets of self‐regulation (including self‐control and emotional processes as well as response inhibition). In terms of the macrostructure of the network, the authors observed stronger connections within the two clusters of self‐regulation and executive functions than between them.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Dutra et al (2022) found that two forms updating (i.e., working memory and short-term memory) were independently associated with self-regulation in 8-to 13-year-old children from low-and middle-income countries, even when controlling for schooling and location effects. Using network models in a lifespan sample, Neubeck et al (2022) found stronger connections within clusters of self-regulation and executive function measures than between them.…”
mentioning
confidence: 98%
“…Using network models in a lifespan sample, Neubeck et al. (2022) found stronger connections within clusters of self‐regulation and executive function measures than between them. Importantly, older adults demonstrated more connections between both constructs than younger individuals, suggesting that the two constructs may tap increasingly overlapping abilities in older people.…”
mentioning
confidence: 99%
“…Multi-dimensional eating behaviors, including emotional eating (EE: i.e., overeating associated with negative emotions), can be separately assessed using the Three-Factor Eating Questionnaire (TFEQ), along with uncontrolled eating (UE, i.e., general difficulties in regulating eating, including hunger) and cognitive restraint (CR, i.e., conscious restriction of food intake to control weight) (12,13). However, only one study that examined the association between grit and eating behavior, as assessed by the TFEQ, measured only cognitive restraint and not the association in with emotional and uncontrolled eating (14). More importantly, to date, there is a lack of research on the extent to which multidimensional eating behaviors mediate the relationship between low grit and obesity.…”
Section: Introductionmentioning
confidence: 99%